Who’s slipping through the cracks? A comprehensive individual, clinical, and health system characterization of people with virologic failure on first-line HIV treatment in Uganda and South Africa - Reynolds, Z; McCluskey, SM; Moosa, MYS; Gilbert, RF; Pillay, S; Aturinda, I; Ard, KL; Muyindike, W; Musinguzi, N; Masette, G; Moodley, P; Brijkumar, J; et al. (HIV medicine, 2022)
Objective: HIV virological failure remains a major threat to programme success in sub-Saharan Africa. While HIV drug resistance (HIVDR) and inadequate adherence are the main drivers of virological failure, the individual, clinical and health system characteristics that lead to poor outcomes are not well understood. The objective of this paper is to identify those characteristics among people failing first-line antiretroviral therapy (ART Methods: We enrolled a cohort of adults in HIV care experiencing virologic failure on first-line antiretroviral therapy (ART) at five sites and used standard statistical methods to characterize them with a focus on three domains: individual/demographic, clinical, and health system, and compared each by country of enrollment. Results: Of 840 participants, 51% were women, the median duration on ART was 3.2 years (IQR, 1.1, 6.4) and the median CD4 cell count prior to failure was 281/mm3 (IQR 121, 457). Half of participants (53%, 95% CI, 0.49-0.56) stated they had greater than 90% adherence and 75% (95% CI, 0.72-0.77) take their ART on time all or most of the time. Conversely, the vast majority (90%, 95% CI, 0.86-0.92) with a completed genotypic drug resistance test had any HIVDR. This population had high health system use, reporting a median of 3 (IQR, 2,6) healthcare visits and a median of 1 (IQR, 1,1) hospitalization in the preceding 6 months. Conclusion: Patients failing first-line ART in sub-Saharan Africa generally report high rates of adherence to ART, have extremely high rates of HIVDR and utilize significant health-care resources. Health systems interventions to promptly detect and manage treatment failure will be a prerequisite to establishing control of the HIV epidemic.
Keywords: HIV drug resistance; Treatment failure; Virologic failure; Africa; First-line